Tinjauan Hukum tentang Notaris yang Melanggar Kode Etik Profesi dalam Penyusunan Akta Jual Beli Saham - Chusnul Hotimah; Ahmad Tarmidi (CV Rewang Rencang, 2025)
This legal review discusses the violation of the notary's code of ethics in making a deed of sale and purchase of shares, specifically based on Supreme Court Decision 15K/Pid/2020. The notary violated the code of ethics by not initialing the deed by the person appearing, the buyer, and the seller, which violates Article 16 paragraphs 7 and 8 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries and the prohibition of notaries at the Extraordinary Congress of the Indonesian Notary Association. This violation not only damages the integrity of the notary profession but can also cause losses to the parties involved in the share sale and purchase transaction. Sanctions given to notaries who violate the code of ethics can be in the form of reprimands, warnings, temporary dismissal, or dismissal from membership of the Indonesian Notary Association. To improve the integrity of the notary profession, efforts need to be made to improve understanding of the code of ethics and increase supervision of notaries. Thus, this study is expected to contribute to a better understanding of violations of the notary code of ethics and their implications for the notary profession.